1990
DOI: 10.1177/016555159001600603
|View full text |Cite
|
Sign up to set email alerts
|

Use of words and phrases from full text in abstracts

Abstract: Comparison of 39 full texts of articles in the ONTAP Computer database with their abstracts showed (1) no significant relationship between abstract length and full-text length, (2) a small, but significant, tendency for abstract words and phrases to concentrate at the beginning of the full text, (3) little use in abstracts of longer verbatim word sequences from full texts. Additional results using the RightWriter style checker are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…First, an earlier study (Craven, 1991a) had shown little use in abstracts of longer verbatim word sequences from full texts. First, an earlier study (Craven, 1991a) had shown little use in abstracts of longer verbatim word sequences from full texts.…”
Section: Introductionmentioning
confidence: 99%
“…First, an earlier study (Craven, 1991a) had shown little use in abstracts of longer verbatim word sequences from full texts. First, an earlier study (Craven, 1991a) had shown little use in abstracts of longer verbatim word sequences from full texts.…”
Section: Introductionmentioning
confidence: 99%